Ketahanan Keluarga dalam Perspektif al-Qur’an: Fondasi Spiritual di Tengah Dinamika Zaman - Syahfitri Pasaribu; Islamiyah (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2025)
Modern families face significant challenges to their stability and harmony due to globalization, shifting social values, and technological advances. Increasing divorce rates, lack of communication, and erosion of spiritual values ??are crucial issues. In Islam, the family is seen as the foundation for the formation of morals and faith. The Qur'an emphasizes the importance of building a strong (sakinah), harmonious family based on divine values, as explained in QS. Ar-Rum: 21 on the concept of sakinah, mawaddah, and rahmah. Family resilience is a holistic concept that includes physical, economic, and especially spiritual dimensions. Spiritual strength is a solid foundation for facing the pressures of life. Islam provides rules for maintaining family harmony, such as Al-'Adah Muhakkamah and Ad-Dharu Yuzal. The Qur'an offers a long-term solution through a spiritual approach, with the value of monotheism as the main principle. The family is the center of internalization of values, and parents act as role models. The Qur'anic solution includes reviving spiritual values ? (QS. Luqman: 13), building healthy communication, and affirming roles according to Islamic nature. By adhering to the Qur'an, Muslim families can maintain their integrity amidst the dynamics of the times.